Age and sex-related differences in the haematological parameters of captive African grey parrots (Psittacus erithacus) - Gaspar, Helena; Bargallo, Ferran; Grifols, Jordi; Correia, Elisete; de Lurdes Pinto, Maria (Veterinarni medicina, 2021)
African grey parrots (Psittacus erithacus) are very popular pets, commonly seen in avian clinical practice. Haematological profiles are critical to the understanding of several disease processes, being particularly useful as diagnostic tools in clinical practice, since birds tend to hide clinical signs of disease. We have previously proposed new haematological reference intervals (RI) for captive African grey parrots, and in the present work the basic data obtained was studied in detail to investigate the influence of factors, such as age and sex, on the haematological profile of this bird species. During an 8-year period (March 2009 to July 2017), animals (n = 239) examined in first consultations or check-ups at the Zoològic Veterinaris (Barcelona) were submitted to blood collection at different time points, rendering a total of 459 blood samples. The haematological testing was performed according to the guidelines of the American Society of Veterinary Clinical Pathology to determine the packed cell volume (PCV), haemoglobin (Hb), mean haemoglobin concentration (MHC), mean corpuscular volume (MCV), mean corpuscular haemoglobin concentration (MCHC), total erythrocyte count (TRBC), total leukocyte count (TWBC), and differential leukogram with absolute and relative counts. All the haematological testing was performed in an in-house laboratory as previously described. Animals with 0 to 4 years of age showed higher values of PCV (P < 0.001), Hb (P = 0.023) and RBC (P = 0.018), and lower values of MCHC (P = 0.008), WBC (P = 0.012) and heterophils (P < 0.001) than older animals. There were significant differences exhibited in the monocytes (P = 0.035) between different age groups. Females presented higher PCV, Hb and RBC values (P < 0.001) compared to males. Our results suggest that the age and sex influence the haematological parameters in a significant manner in African grey parrots and should be accounted for when assessing the health status of individuals from this species.
Keywords: avian medicine; blood cell count; physiology; exotic pets